PENGARUH PEMANASAN FILTRAT RIMPANG KUNYIT (CURCUMA LLONGA) TERHADAP PERTUMBUHAN KOLONI BAKTERI COLIFORM SECARA IN VITRO - NANANG FITONI, CHOLIB (Universitas Negeri Surabaya, 2013)
Turmeric (Curcuma longa) is one of the potential medicinal plants, because it is useful as antioxidant and antibacterial. The purpose of this research was to describe the effect of heating turmeric on the growth of colonies of coliform bacteria in vitro. The parameter was the number of coliform bacteria colonies that grown on EMB Agar media that was used in the research. The research was carried out experimentally using a completely randomized design with 3 treatments. The first treatment was turmeric filtrate without heating. The second treatment was turmeric filtrate with temperature 90oC heating for 10 minutes. The third treatment was not using turmeric filtrate as a control. All three treatments were repeated six times to obtain the 18 treatment combinations. Parameters measured were the number of coliform bacteria colonies that grown on EMB Agar media that have given various treatments. Data analysis was using descriptive analysis. The results showed that addition of turmeric filtrate could hinder the growth of colonies of coliform bacteria. This shown by a decrease in the number of coliform bacteria colonies growing on treatment with the addition of turmeric filtrate compared to the control treatment. Giving filtrate turmeric without heating provides optimal results in inhibiting the growth of total coliform bacteria colonies.   Key words: coliform bacteria; filtrate turmeric; heating temperature